2017
DOI: 10.48550/arxiv.1702.01731
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Deep Convolutional Neural Network for Background Subtraction

Abstract: In this work, we present a novel background subtraction system that uses a deep Convolutional Neural Network (CNN) to perform the segmentation. With this approach, feature engineering and parameter tuning become unnecessary since the network parameters can be learned from data by training a single CNN that can handle various video scenes. Additionally, we propose a new approach to estimate background model from video. For the training of the CNN, we employed randomly 5% video frames and their ground truth segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Since camera traps are static, detecting animals in the images could be considered either a change detection or foreground detection problem. Detecting changes and/or foreground vs. background in video is a well studied problem [36], [37]. Many of these methods rely on constructing a good background model that updates regularly, and thus degrade rapidly at low frame rates.…”
Section: Detectionmentioning
confidence: 99%
“…Since camera traps are static, detecting animals in the images could be considered either a change detection or foreground detection problem. Detecting changes and/or foreground vs. background in video is a well studied problem [36], [37]. Many of these methods rely on constructing a good background model that updates regularly, and thus degrade rapidly at low frame rates.…”
Section: Detectionmentioning
confidence: 99%
“…This method achieved an average F-Measure of 0.9046 † † The values are obtained from their paper. [13] trained their model all at once by combining training frames from various video sequences; in particular, including 5% of frames from each video sequence. They followed the same training procedure as in [12], in which image-patches were combined with background-patches then fed to the network.…”
Section: Related Workmentioning
confidence: 99%
“…A common method for segmenting moving objects in a scene is to perform a background subtraction, in which moving objects are considered as foreground pixels and non-moving objects are considered as background pixels. This binary classification problem has been extensively studied and improved over the years, and several approaches have been proposed concurrently [7][8][9][10][11][12][13][14][15]. There are many challenges in developing a robust background subtraction algorithm: sudden or gradual illumination changes, shadows cast by foreground objects, dynamic background motion (waving tree, rain, snow, air turbulence), camera motion (camera jittering, camera panning-tilting-zooming), camouflage or subtle regions, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, both CNN and foreground attentive neural network (FANN) models have been developed to perform foreground segmentation [62], [63]. In addition to conventional Gaussian mixture model-based background subtraction, recent explorations have also shown that CNN models could be effectively used for the same purpose [64], [65]. To address these separated foreground objects and background attributes, Zhang et al [66] introduced a new background mode to more compactly represent background information with better R-D efficiency.…”
Section: Overview Of Dnn-based Video Pre-processingmentioning
confidence: 99%